Formulation of Emulsion with a Combination of Microalgae Chlorella sp. with Gourami Fish Oil (Osphronemus gouramy L.) - Utari, Widi Gustita; Alfayzah, Faradillah; Junaida, Alfini; Maharani, Della Shinta; Pratama, Muhammad Imran Ade; Pratiwi, Eskarani Tri (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2024)
Introduction:. Chlorella sp. is a type of microalgae that has high nutritional value and is often cultivated for various purposes such as medicines or supplements. One of the efforts that can be made to optimize the benefits of Chlorella sp. microalgae with a combination of gourami fish oil formulated in an emulsion reparation. Aims: determine the best formula and physical stability of Chlorella sp. microalgae emulsion with gourami fish oil. Method: making emulsion with varying concentrations of Chlorella sp. microalgae with gourami fish oil (F1= 1:1, F2= 2:1, and F3=3:1). The physical preparation stability test will be carried out such as organoleptic test, homogeneity, pH, viscosity, emulsion type and stability. Results: all three formulas met the requirements for physical evaluation of emulsion preparations, only in the stability test there was separation at F3 (3:1). The type of emulsion produced is oil in water (O/W). Conclusion: the best formula according to the test results is F1 & F2.